2013
DOI: 10.1063/1.4770057
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical bonding and magnetic exchange in two-dimensional [M(TCNE)(NCMe)2]X (M = Fe, Mn; X = FeCl4, SbF6) magnets: A pressure study

Abstract: Pressure-dependent X-ray diffraction studies reveal the bulk modulus and compression anisotropy of the 2D magnet [Mn(TCNE)(NCMe)(2)]SbF(6). The Raman response of this and the similar [Fe(TCNE)(NCMe)(2)]FeCl(4) layered magnet, shows that the evolution of the a(g) ν(C=C) frequency correlates well with the magnetic exchange and T(c) variations of these materials under pressure. There is a significantly more complex correlation between the a(g) ν(C≡N) frequency and T(c) despite the fact that some unpaired π* elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Recently we have shown that the unit cell volume of 3 varies continuously with pressure up to 2 GPa with a bulk modulus K = −V(dP/dV) = 10.4 GPa. The main change in the unit cell volume occurs interlayer distance while Mn-µ 4 -TCNE layers remain relatively rigid reflecting the two-dimensional character of the network [24]. The observed differences in the intra-and interlayer structural parameters of 1 and 3 (3% volume and 2.3% interlayer distance decrease, respectively) due to the anion size change are consistent with the 'chemical pressure' effect corresponding to ∼0.5-0.6 GPa hydrostatic pressure application [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we have shown that the unit cell volume of 3 varies continuously with pressure up to 2 GPa with a bulk modulus K = −V(dP/dV) = 10.4 GPa. The main change in the unit cell volume occurs interlayer distance while Mn-µ 4 -TCNE layers remain relatively rigid reflecting the two-dimensional character of the network [24]. The observed differences in the intra-and interlayer structural parameters of 1 and 3 (3% volume and 2.3% interlayer distance decrease, respectively) due to the anion size change are consistent with the 'chemical pressure' effect corresponding to ∼0.5-0.6 GPa hydrostatic pressure application [24].…”
Section: Resultsmentioning
confidence: 99%
“…The main change in the unit cell volume occurs interlayer distance while Mn-µ 4 -TCNE layers remain relatively rigid reflecting the two-dimensional character of the network [24]. The observed differences in the intra-and interlayer structural parameters of 1 and 3 (3% volume and 2.3% interlayer distance decrease, respectively) due to the anion size change are consistent with the 'chemical pressure' effect corresponding to ∼0.5-0.6 GPa hydrostatic pressure application [24]. However, the magnetic studies of 3 under pressure have shown a sizable (up to 5%) increase of T c at 0.6 GPa.…”
Section: Resultsmentioning
confidence: 99%